1994
DOI: 10.1172/jci117378
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor improves myocardial function in chronically ischemic porcine hearts.

Abstract: The effect of basic fibroblast growth factor (bFGF) administration on regional myocardial function and blood flow in chronically ischemic hearts was studied in 26 pigs instrumented with proximal circumflex coronary artery (LCX) ameroid constrictors. In 13 animals bFGF was administered extraluminally to the proximal left anterior descending (LAD) and LCX arteries with heparin-alginate beads and 13 other animal served as controls. bFGF-treated pigs showed a fourfold reduction in left ventricular infarct size com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
144
1
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(150 citation statements)
references
References 47 publications
3
144
1
2
Order By: Relevance
“…Recent studies have demonstrated the therapeutic potential of administering FGF-2 to augment revascularization of the ischemic limb or myocardium [1,12,18,301, FGF-2 administered by repeat intramuscular injection or intra-arterial infusion has been shown to substantially increase collateral development in the ischemic area or improve the symptoms. Therefore, it is reasonable to suppose that FGF-2 could enhance angiogenesis in necrotic or avascular bone as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated the therapeutic potential of administering FGF-2 to augment revascularization of the ischemic limb or myocardium [1,12,18,301, FGF-2 administered by repeat intramuscular injection or intra-arterial infusion has been shown to substantially increase collateral development in the ischemic area or improve the symptoms. Therefore, it is reasonable to suppose that FGF-2 could enhance angiogenesis in necrotic or avascular bone as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the therapeutic potential of administering the FGF-2 to augment revascularization of the ischemic limb [l,l8] or myocardium [12,30]. In addition, FGF-2 is recognized as a potent mitogen for a variety of mesenchyrnal cells [11,22].…”
Section: € -T I I D Uddrcs\mentioning
confidence: 99%
“…Recently, therapeutic angiogenesis that is based on exogenous administration of angiogenic growth factors has emerged as a promising strategy for the treatment of tissue ischemia (Lee et al, 2000b;Kim et al, 2004). The potential of therapeutic angiogenesis has been validated in various animal models of limb or myocardial ischemia and recently in patients treated with VEGF and bFGF Harada et al, 1994;Kim et al, 1994;Unger et al, 1994;Lazarous et al, 1996;Koh et al, 2002;Yamamoto et al, 2003;Hughes et al, 2004). Gene transfer can be an effective means to provide localized delivery of a high concentration of angiogenic growth factors to the ischemic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The growth factors that have been investigated for new blood vessel formations are the vascular endothelial growth factors (VEGF) (5-7), fibroblast growth factors (8,9), and the angiopoietins (10). One of the most widely studied vascular growth factors is VEGF, a homodimeric heparin-binding glycoprotein of [34][35][36][37][38][39][40][41][42][43][44][45][46].…”
mentioning
confidence: 99%
“…VEGF injected intravenously has been shown to improve myocardial blood flow, but it also results in hypotension as a side effect (17). Alternatively, VEGF and fibroblast growth factor have been injected directly into the coronary arteries (6,8,9). The angiogenic effect appears to be transient, because most of the angiogenic factors are not retained in the heart.…”
mentioning
confidence: 99%